Preparation and modification of mediumchain- length poly(3 Hydroxyalkanoates) as osteoconductive and amphiphilic porous scaffold / Nor Faezah Ansari - Nor Faezah , Ansari (2017)
Polyhydroxyalkanoates (PHA) are hydrophobic biopolymers with huge potential for biomedical applications due to their biocompatibility, excellent mechanical properties and biodegradability. A porous composite scaffold made of medium-chainlength poly(3-hydroxyalkanoates) (mcl-PHA) and hydroxyapatite (HA) was fabricated using particulate leaching technique and NaCl as porogen. Different percentages of HA loading was investigated that would support the growth of osteoblast cells. Ultrasonic irradiation was applied to facilitate the dispersion of HA particles into mcl-PHA matrix. Different P(3HO-co-3HHX)/HA composites were investigated using Field Emission Scanning Electron Microscopy (FESEM), X-ray Diffraction (XRD), Fourier Transform Infrared Spectra (FTIR) and Energy Dispersive X-ray Analysis (EDXA). The scaffolds were found to be highly porous with interconnecting pore structures and HA particles were homogeneously dispersed in the polymer matrix. The scaffolds biocompatibility and osteoconductivity were also assessed following the proliferation and differentiation of osteoblast cells on them. From the results, it is clear that scaffolds made from P(3HO-co-3HHX)/HA composites are viable candidate materials for bone tissue engineering applications. Additionally, glycerol 1,3-diglycerol diacrylate (GDD) was graft copolymerized onto poly(3-hydroxyoctanoate-co-3-hydroxyhexanoate) P(3HO-co- 3HHX) to render the latter more hydrophilic. Grafting of P(3HO-co-3HHX) backbone was performed using benzoyl peroxide as free radical initiator in homogenous acetone solution. The graft copolymer of P(3HO-co-3HHX)-g-GDD was characterized using spectroscopic and thermal methods. The presence of GDD monomer in the grafted P(3HO-co-3HHX) materials linked through covalent bond was indicated by spectroscopic analyses. Different parameters affecting the graft yield viz. monomer concentration, initiator concentration, temperature and reaction time were also investigated. Water uptake measurement showed that P(3HO-co-3HHX)-g-GDD copolymer became more hydrophilic as the GDD concentration in the copolymer increased. Introduction of hydroxyl groups via grafted GDD monomers improved the wettability and imparted amphiphilicity to the graft copolymer, thus potentially improving their facility for cellular interaction. Thermal stability of grafted copolymer reduced with increased grafting yield. The activation energy, Ea, for the graft copolymerization was calculated at ~ 51 kJ mol-1. Mechanism of grafting reaction was also proposed in the study. Scaffolds of P(3HO-co-3HHX)-g-GDD/HA were successfully fabricated via graft copolymerization and physical blend in order to improve the hydrophilicity of the mcl-PHA. FTIR analysis showed the presence of new absorption spectra for –OH and PO which indicated the presence of GDD and HA in mcl-PHA structure, respectively. EDX analysis was applied to ratify the distribution of HA particles within the P(3HO-co-3HHX)-g-GDD/HA composite matrix. Toxicity of the composite was studied against Artemia franciscana in brine shrimp lethality assay (BSLA). No significant mortality of the test organism was recorded, thus implied that the novel scaffold poses negligible toxicity risk to the cell. It is concluded that P(3HOco- 3HHX)-g-GDD/HA composite is potentially useful for biomedical applications.